Heberprot-p® and ozone therapy in the treatment of diabetic foot ulcers: a bibliographic review (Research, Society and Development, 2021)
Introduction: Diabetes Mellitus (DM) is a public health issue as it represents the 3rd largest cause of death in the world, it causes several complications for the lives of its patients, including the diabetic foot, which has a great impact on the quality of life of the patient, and it is noteworthy that the treatment has a high financial cost. Describe the effectiveness of ozone therapy and Heberprot-P® in the treatment of diabetic foot ulcers. Methodology:  The search for scientific articles was performed in electronic databases: Scientific Electronic Library Online (SCIELO), Latin American Literature on Health Sciences (LILACS), National Library of Medicine and the National Institute of Health (Pubmed). Results and Discussion: When uncontrolled, in the long term, DM can lead to several complications, such as the diabetic foot, which is characterized by lesions on the individual's feet caused by the peculiar triad of DM: neuropathy, peripheral vascular disease and infection. The proper treatment of Diabetic Foot depends on a thorough clinical evaluation and a multidisciplinary team, which will provide counseling, treatment and follow-up. Final Considerations: The treatment of diabetic foot with Heberprot-P® and ozone therapy has been shown to be highly effective and cheaper than conventional treatments. Both present speed in the wound healing process, and a reduction in the length of hospital stay, as well as a reduction in the need for limb amputation. Remember that ozone therapy should not be used as a single treatment, but always in combination with another type of treatment.